Interaksi Guru dan Siswa dalam Pembinaan Disiplin Siswa pada Pembelajaran Pendidikan Pancasila dan Kewarganegaraan - Emilia Dewita; Junaidi Indrawadi (Universitas Negeri Medan, 2020)
This article aims to find out how the interaction of teachers and students in developing student discipline in citizenship learning at SMK Negeri 5 Padang. The method used in this research is descriptive qualitative approach by collecting data through observation, interviews and literature studies. The results of this study indicate that the discipline character of students at SMK Negeri 5 Padang is still not good despite the formation of discipline character by the citizenship teacher. The process of teacher and student interaction in fostering the character of student discipline at SMK Negeri 5 Padang through four stages, namely 1) making rules / agreements in learning citizenship between citizenship teachers and students, 2) Implementation of discipline by students, 3) punishment for students who violate disciplines in citizenship learning and 4) Coaching follow-up. Through this research, it is expected that efforts to increase teacher and student interaction and self-improvement / personality of students, teachers must provide instructions, how to implement discipline properly, provide guidance and assistance to students. This study recommends further research on self-concept in discipline so that it becomes a habit in students.